A comparative study of conventional and supercritical carbon dioxide extraction methods for the recovery of bioactive compound from Lion’s Mane mushroom (Hericium erinaceus) - Joradon Pinida; Rungsardthong Vilai; Ruktanonchai Uracha; Suttisintong Khomson; Iempridee Tawin; Thumthanaruk Benjawan; Vatanyoopaisarn Savitri; Uttapap Dutsadee (E3S Web of Conferences, 2022)
Lion’s Mane mushroom (Hericium erinaceus), LM, is a medicinal mushroom which has various bioactive compounds within its fruiting bodies. However, during the cultivation, a large amount of the irregular-shape LM (Ir-LM) was generated. This mushroom type was considered a mushroom by-product. In this study, conventional solvent extraction (Maceration) and supercritical fluid extraction using carbon dioxide (SCFE-CO2) were performed to compare the recovery of ergosterol, hericenone C, and hericene A content from Reg-LM and Ir-LM fruiting bodies. Furthermore, two extraction conditions (40°C at 200 bar and 70°C at 350 bar) were conducted for the SCFE-CO2 technique. The results showed that SCFE-CO2 methods produced a higher recovery of ergosterol and hericenone C as compared to the Maceration techniques. SCFE-CO2 extracts were determined for their antioxidant activities. The DPPH radical scavenging activity of the extract from 70°C at 350 bar was significantly higher (p < 0.05) than the extract obtained from 40°C at 200 bar. The results revealed the use of green technology supercritical fluid extraction using carbon dioxide to recover bioactive compounds from mushroom by-products and apply for high-value added products.